Formation and development of the language training methodology for foreign students at classical university. Part 4. Language training of foreign medical students in the english medium education format - N. Ushakova; I. Kushnir; O. Trostynska; T. Aleksieienko (Викладання мов у вищих навчальних закладах освіти на сучасному етапі: Міжпредметні зв'язки)
This article continues a series of scientific research focusing on the stages of formation and development of the methodology of language training of foreign higher education students. Specifically, it examines the work of the Language Training Department at the Institute of International Education for Study and Research of V.N. Karazin Kharkiv National University. The objective of the article is to elucidate the system of teaching Ukrainian to foreign medical students pursuing higher education in English and its practical implementation.